Project BHTRM: new strategy of monitoring and acting in spinal cord injuries in the city of Belo Horizonte - Diogo Guilherme de Vasconcelos Gonçalves; Guilherme Zanini Rocha; José Augusto Malheiros; Paula Martins; Aluízio Augusto Arantes Junior; Cristiane Hernandes (Coluna/Columna, 2014)
Objective: The BHTRM Project aims at studying the epidemiology of TRM in the city of Belo Horizonte and providing the means to monitor these patients. Method: To assess the efficacy and solvability of the project, two groups of patients treated at the João XXIII Hospital were compared in two distinct periods. Group 1 - from May 1, 2011 to July 31, 2011, months of project initiation and Group 2 - from December 1, 2012 to February 28, 2013. Results: Despite the 34% increase in the number of assisted patients, there is a 30% drop in the average number of days of hospitalization, as well as a decrease in the average days waiting for surgery of patients requiring surgical treatment, from 10.9 to 4.84, a drop of 56%. Conclusion: BHTRM Project is a useful tool in public health management. It optimizes the treatment of patients with spinal trauma by decreasing the time between admission and surgery. Also provides active monitoring of patient care and ensures better integration of rehabilitation care.